ANALYZING SMARTPHONE EXPERIENTIAL MARKETING OF YOUTH IPHONE USER IN MANADO - Kainde, Shania K.; Lapian, Joyce S.L.H.V.; Saerang, Regina T. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The sophistication of smartphones increasingly sought after by consumers. In order to win the smartphone industry, company not only considering on the quality of the product but also the strategy to selling their product. Experiential marketing is as an activity to do some anticipation, management and achievement of customer satisfaction through the process of exchange which is personal events that occur as response or some stimulus.  The aim of this research is to analyze the customer perception of experiential marketing of iPhone. To achieve this objective, the researcher took the information from 15 informants using qualitative study which is in-depth interview. The result of the study is the five dimensions of experiential marketing affect the customer perception. Through sense experience, feel experience, think experience, act experience and relate experience. Apple Inc is one of the smartphone industry that using experiential marketing as their marketing strategy to attract customer that proved by the interview results. The recommendation for this study can be used as a reference for the development and deepening of knowledge about experiential marketing.Keywords: experiential marketing, iPhone